2016
DOI: 10.1016/j.meatsci.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of proteolytic and physico-chemical characteristics of Norwegian dry-cured ham during its processing

Abstract: Proteolytic activity and physico-chemical characteristics were studied for Norwegian dry-cured ham at four different times of processing: raw hams, post-salted hams (3 months of processing), hams selected in the middle of the production (12 months of processing) and hams at the end of the processing (24 months). Cathepsin H activity decreased until negligible values after 3 months of processing, whereas cathepsins B and B+L were inactive at 12 months. AAP was the most active aminopeptidase whereas RAP and MAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…[13] PI is influenced by many factors such as the amount of added NaCl and endogenous enzymatic activity. [19] The higher (P < 0.05) PI in SS (days 27 and 57, Figure 1) supported by the work of Guo et al [9] and Li et al [20] , found that L -lysine and/or L -histidine increased the myosin solubility. This results from the presence of L -lysine and/or L -histidine changing myosin secondary structure, that exposes the buried hydrophobic and sulphydryl groups to the surface of myosin, and inhibits myosin aggregation in the process.…”
Section: Proteolysis Index (Pi)supporting
confidence: 62%
“…[13] PI is influenced by many factors such as the amount of added NaCl and endogenous enzymatic activity. [19] The higher (P < 0.05) PI in SS (days 27 and 57, Figure 1) supported by the work of Guo et al [9] and Li et al [20] , found that L -lysine and/or L -histidine increased the myosin solubility. This results from the presence of L -lysine and/or L -histidine changing myosin secondary structure, that exposes the buried hydrophobic and sulphydryl groups to the surface of myosin, and inhibits myosin aggregation in the process.…”
Section: Proteolysis Index (Pi)supporting
confidence: 62%
“…The quantification of biomarkers can also be used to follow the time course of ripening, being helpful in product development and process optimization to ensure the quality and safety of dry‐cured ham . In this regard, two peptides were detected as potential biomarkers of the manufacturing process of Norwegian dry‐cured hams . Table shows the sequences of peptides identified as potential biomarkers of the dry‐cured ham processing.…”
Section: Specific Applications Of Peptidomics In Dry‐cured Hammentioning
confidence: 99%
“…In summary, salt diffusion together with other process parameters such as water activity, pH and temperature have been reported to strongly affect muscle enzymes activity (Petrova, Tolstorebrov, Mora, Toldrá & Eikevik, 2016;Toldrá, Rico & Flores, 1993;Flores, Aristoy & Toldrá, 1997). So, Semimembranosus is the external muscle accumulating more salt during the salting step.…”
Section: Resultsmentioning
confidence: 96%